2009
DOI: 10.1148/radiol.2532082324
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MR Phase-corrected Imaging to Investigate Increased Brain Iron Deposition of Patients with Alzheimer Disease

Abstract: Iron concentration in the PC was positively correlated with the severity of AD patients' cognitive impairment, indicating that it may be used as a biomarker to evaluate the progression of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 34 publications
6
91
0
4
Order By: Relevance
“…Coincidently, in previous studies, (Sullivan et al, 2009;Zhu et al, 2009) increased iron levels were found both in the cortex and cerebellum from the preclinical AD cases. Moreover, iron concentrations have been found to be increased in the bilateral hippocampus, parietal cortex, frontal white matter, putamen, caudate nucleus, thalamus, red nucleus, substantia nigra, and dentate nucleus subregions of patients with diagnosed AD and in normal elderly patients (Sullivan et al, 2009;Zhu et al, 2009). It is important to note that these brain iron concentrations, particularly those in the parietal cortex at the early stages of AD, have been found to positively correlate with the severity of patient's cognitive impairment (Zhu et al, 2009).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Coincidently, in previous studies, (Sullivan et al, 2009;Zhu et al, 2009) increased iron levels were found both in the cortex and cerebellum from the preclinical AD cases. Moreover, iron concentrations have been found to be increased in the bilateral hippocampus, parietal cortex, frontal white matter, putamen, caudate nucleus, thalamus, red nucleus, substantia nigra, and dentate nucleus subregions of patients with diagnosed AD and in normal elderly patients (Sullivan et al, 2009;Zhu et al, 2009). It is important to note that these brain iron concentrations, particularly those in the parietal cortex at the early stages of AD, have been found to positively correlate with the severity of patient's cognitive impairment (Zhu et al, 2009).…”
Section: Discussionsupporting
confidence: 71%
“…The intracellular pool of free iron, the labile iron pool (LIP), has been well established to modulate the expression of various proteins, including the amyloid precursor protein (Frackowiak et al, 2009;Cho et al, 2010). Coincidently, in previous studies, (Sullivan et al, 2009;Zhu et al, 2009) increased iron levels were found both in the cortex and cerebellum from the preclinical AD cases. Moreover, iron concentrations have been found to be increased in the bilateral hippocampus, parietal cortex, frontal white matter, putamen, caudate nucleus, thalamus, red nucleus, substantia nigra, and dentate nucleus subregions of patients with diagnosed AD and in normal elderly patients (Sullivan et al, 2009;Zhu et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although various factors other than iron content also affect the estimated iron concentration in the brain on MRI, MRI is used to diagnose many kinds of iron-storage diseases, such as neurodegeneration with brain iron accumulation (NBIA) [65][66][67][68], Alzheimer's disease [69,70], Parkinson's disease [71,72], multiple sclerosis [73,74], Friedreich's ataxia [75,76], and Huntington's disease [53,77]. NBIA is a group of neurodegenerative diseases characterized by iron accumulation in the basal ganglia.…”
Section: Ironmentioning
confidence: 99%
“…It has been demonstrated that abnormal iron accumulation occurs in the brains of patients with various neurodegenerative diseases such as IPD, multiple system atrophy, Alzheimer disease, and MS. [2][3][4][5] Parkinsonism is a clinical syndrome characterized by tremors, muscle rigidity, and bradykinesia. While the most prevalent form of parkinsonism remains IPD, other secondary causes exist, such as some metabolic diseases and side effects of several medications and toxins.…”
mentioning
confidence: 99%